IMPROVING MASTERY OF MUFRODAT (VOCABULARY) BY USING FLASHCARD MEDIA FOR STUDENTS IN CLASS VII SMP PESANTREN PUTRI YATAMA MANDIRI GOWA - Feni Hariyanti; Syamsu Rijal; Sitti Mutmainnah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the process and results of the application of flashcard media in improving mastery of mufrodat (Arabic vocabulary). This type of research is Classroom Action Research (PTK). The subject of the research was the seventh grade students of SMP Pesantren Putri Yatama Mandiri Gowa with a total of 28 people. Data collection techniques used in the study were test sheets and observation sheets. This research was conducted in 2 cycles and each cycle consisted of 2 meetings. The results of this study indicate that the average score obtained by students has increased. In cycle I, the average value was 69% and the average value in cycle II was 91%. The average score obtained by students in learning mufrodat by using flashcards media increased by 22% from the value of cycle I to the value of cycle II.